Implementation of Training Design to Improve Teacher Competence Based on Googleform Journal Teacher Agenda in SMPN 27 Pesawaran - Sari, Melian; Firdaus, Rangga; Riswandi, Riswandi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Professional teachers are the main determinants of educational success. One indicator of teacher professional competence is the ability to manage teaching and learning programs using the use of information technology. The reality of teacher professionalism in the learning process at this time is still diverse, one of which is that teachers have not been able to show good performance. To measure teacher performance, supervision is carried out by the principal, as one of the steps to monitor and provide direct follow-up on the teacher's performance. Based on the findings of the researchers, it is known that the inability of teachers to show good performance is influenced by the lack of information, design, implementation in improving the professional performance of teachers, especially in teacher competencies based on google form, for this reason teacher competency training is needed. This research uses the method method (SLR). regarding research methods: "Literature" which means it is a critical analysis of the research that is being carried out on a special topic or in the form of a question to a part of science. helps us in compiling a framework that is in accordance with the theory, findings, and results of previous research in solving the problem formulation in the research that we make. The SLR method is used to identify, review, evaluate and interpret all available research with the topic area of the phenomenon of interest, with specific relevant research questions. With the use of the SLR Method, a systematic review and identification of journals can be carried out. The results that researchers find are basically training is a series that guides, guides and develops something that previously did not know to be known by someone, the hope is that the training of google foam-based teacher competencies can support teacher performance as a driving force in the successful implementation of learning